Satisfaction And Contribution Of Stakeholders From The Performance Prism Model - Elizandra Severgnini; Edwin Vladimir Cardoza Galdaméz; Romildo de Oliveira Moraes (BBR: Brazilian Business Review)
In the process of performance evaluation it is essential to define the needs, capacities and contributions of stakeholders. The objective of this paper is to analyze the perception of managers of Micro, Small and Medium Enterprises (SMEs) in relation to the Satisfaction and Contribution of Stakeholders to organizational performance. The research was conducted with 7 SMEs. The results from the interviews showed that (i) there is a broader understanding of who are the most important stakeholders, opposing the view of the owners and customers and (ii) the contribution of stakeholders expected by the business is more subjective, considering the continuity of the relationship with the parties and a delivery of superior value. Finally, the results provided the basis for the proposition of new dimension called Expectations of Continuity and Partnership as an element to assess stakeholder contribution.